Abundance of Tule Geese Anser albifrons elgasi in the Pacific Flyway 2003-2019 - Yparraguirre, Dan R.; Sanders, Todd A.; Weaver, Melanie L.; Skalos, Daniel A. (Wildfowl, 2025)
Tule Greater White-fronted Geese Anser albifrons elgasi (Tule Geese) may be the least abundant of North American goose subspecies and thus are a conservation concern.Â  However, existing Tule Goose abundance estimates are either outdated, unpublished or lack estimates of precision. Annual estimates of Tule Goose abundance were derived by expanding estimates of radio-marked goose abundance by the ratio of total to radio-marked geese from mark-resight data. Tule Geese (n = 1,160) were captured and ringed during 2003–2019 primarily at an autumn migration stopover area in eastern Oregon, and 505 were also marked with plastic collars with unique codes and VHF radios. About 19,900 resightings (live encounter by radio telemetry or visual sightings) of radio-marked Tule Geese were made, primarily during autumn and winter in Oregon and California. The mean (± s.e.) annual abundance of Tule Geese in the autumn was 14,703 ± 1,455 (95% CI = 11,852–17,555, n = 17). There was no evidence of a trend in Tule Goose abundance during this period; the annual growth rate was -1.89 ± 1.84% (95% CI = -5.63–2.0, t16 = 1.05, P = 0.311, n.s.). Point estimates of annual abundance were variable (range = 6,992–33,342) and lacked precision (mean CV = 26%, range = 19–41%). The uncertainty was primarily associated with the variance of total to marked goose ratio estimates compared to estimates of radio-marked goose abundance. Winter distribution of Tule Geese generally appears to be unchanged from information from the 1980s and 1990s. Mean annual survival probability was lower for female (0.724 ± 0.038, 95% CI = 0.643-0.792) than for male (0.823 ± 0.029, 95% CI = 0.758–0.874) leg-ringed only geese, and for radio-marked geese (0.610 ± 0.028, 95% CI = 0.553–0.664) compared to leg-ringed only geese (0.786 ± 0.027, 95% CI = 0.727–0.834). The mark-resight method provides a means to monitor abundance of Tule Geese; however, improvements are needed to increase the precision of estimates, particularly regarding estimation of the ratio of total to marked geese. The stable trend in abundance and the moderate survival rates suggest that managers may need to assess current management strategies carefully if Tule Geese abundance is to be maintained or increased.